(untitled) (Semiárida, 2020)
Buffelgrass (Cenchrus ciliaris L) seeding is a practice currently used for rapid restoration of grass cover on degraded areas at the Arid Chaco region. Invasion of native woody species is a generalized fact on this kind of pasture. Cattle-goat simultaneous grazing could be a strategy to improve vegetation utilization and increase animal production. The objective of this study was to evaluate goat stocking rate effects on diet composition and similarity between cattle and goats during the growing season (November to April) in woody encroached buffelgrass pastures. Three treatments were evaluated (T1=1.00 goat/ha, T2=1.71 goat/ha y T3=2.42 goat/ha). Each treatment was simultaneous grazed by heifers (0.86 head/ha). Fecal samples of 6 goats and 6 heifers were monthly (from December-10-2005 to May-62006) recovered in each treatment. Diet botanical composition was evaluated by microhistological analysis. Within each animal species, differences (p<0.05) were detected in diet composition and similarity among stocking rates. Within each stocking rate, differences (p<0.05) were detected in diet composition between animal species but not (p>0.05) in diet similarity. Results show that, in similar environments to the present study, goat stocking rate is an important factor that affects food selection and that for this reason, it should be considered when designing multispecies grazing strategies for improving vegetation utilization and increasing animal production.